Decreased Erythrocyte NA+, K+-ATPase Activity and Increased Plasma TBARS in Prehypertensive Patients. (1st August 2012) - Malfatti, Carlos Ricardo Maneck; Burgos, Leandro Tibiriçá; Rieger, Alexandre; Rüdger, Cássio Luiz; Túrmina, Janaína Angela; Pereira, Ricardo Aparecido; Pavlak, João Lang; Silva, Luiz Augusto; Osiecki, Raul
Abstract : The essential hypertension has been associated with membrane cell damage. The aim of the present study is investigate the relationship between erythrocyte Na +, K + -ATPase and lipoperoxidation in prehypertensive patients compared to normotensive status. The present study involved the prehypertensive patients (systolic: 136 ± 7 mmHg; diastolic: 86.8 ± 6.3 mmHg; n = 8 ) and healthy men with normal blood pressure (systolic: 110 ± 6.4 mmHg; diastolic: 76.1 ± 4.2 mmHg; n = 8 ) who were matched for age (35 ± 4 years old). The venous blood samples of antecubital vein (5 mL) were collected into a tube containing sodium heparin as anticoagulant (1000 UI), and erythrocyte ghosts were prepared for quantifying Na +, K + -ATPase activity. The extent of the thiobarbituric acid reactive substances (TBARS) was determined in plasma. The statistical analysis was carried out by Student's t -test and Pearson's correlation coefficient. A P < 0.05 was considered significant. The Na +, K + -ATPase activity was lower in prehypertensive patients compared with normotensive subjects (4.9 versus 8.0 nmol Pi/mg protein/min; P < 0.05 ). The Na +, K + -ATPase activity correlated negatively with TBARS content (r = - 0.6 ; P < 0.05 ) and diastolic blood pressure (r = - 0.84 ; P < 0.05 ). The present study suggests that Na +, K + -ATPase activity reduction and elevation of the TBARS content may underlie the pathophysiological aspects linked to the prehypertensive status.